GENETIC IDENTIFICATION FOR TUNA AND RAINBOW RUNNER CAPTURE IN NORTH BALI WATERS - Gusti Ngurah Permana; Jhon Harianto Hutapea; Haryanti Haryanti; Sari Budi Moria Sembiring; Akio Nakazawa (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2006)
Gondol Research Institute for Mariculture identification of tuna and rainbow runner was an objective in this current study. Samples of five species were collected from territorial water of North Bali. The method used in this study was allozyme electrophoresis. The results showed that buffer of CAPM-6 (citric acid aminoprophylmorpholine) resulted in a sharp and clear banding pattern. The species could be differentiated in six diagnostic isozyme patterns Idh* (isocitrate dehydrogenase), 6Pgd* (6 phosphogluconate dehydrogenase), Gpi* (glucose phosphate isomerase), Mdh* (malate dehydrogenase), Est* (esterase), and Sp* (sarcoplasmic protein). All species were in Hardy-weinberg equilibrium. Heterozygosities of species were ranged from 0.00 to 0.099. Yellowfin tuna has the highest heterozigosity compared with the other species. Clustering samples according to pairs revealed that genetic distance of Bullet tuna (A. rochei) and Eastern little tuna (E. affinis) had small value (0.001). By contrast, the largest value was observed between yellowfin tuna, T. albacares and rainbow runner, E. bipunnulata (0.007). This value indicated that Bullet tuna (A. rochei) and Eastern little tuna (E. affinis) closed relation, while among yellowfin tuna, skipjack tuna, and rainbow runner, were separated phylogenically.